Direct information retrieval after 3D reconstruction in grating‐based X‐ray phase‐contrast computed tomography. (27th June 2018) - Wu, Zhao; Gao, Kun; Wang, Zhili; Wei, Chenxi; Wali, Faiz; Zan, Guibin; Wei, Wenbin; Zhu, Peiping; Tian, Yangchao
Abstract : The theoretical framework of the direct information retrieval method is presented in phase‐contrast computed tomography. Numerical simulations are also performed, which reveal that the proposed method provides comparable results of the reverse projection method with short computational time. Furthermore, the compatibility with the existing data preprocessing methods and iterative reconstruction algorithms is discussed. Abstract : Grating‐based X‐ray differential phase‐contrast imaging has attracted a great amount of attention and has been considered as a potential imaging method in clinical medicine because of its compatibility with the traditional X‐ray tube source and the possibility of a large field of view. Moreover, phase‐contrast computed tomography provides three‐dimensional phase‐contrast visualization. Generally, two‐dimensional information retrieval performed on every projection is required prior to three‐dimensional reconstruction in phase‐contrast computed tomography. In this paper, a three‐dimensional information retrieval method to separate absorption and phase information directly from two reconstructed images is derived. Theoretical derivations together with numerical simulations have been performed to confirm the feasibility and veracity of the proposed method. The advantages and limitations compared with the reverse projection method are also discussed. Owing to the reduced data size and the absence of a logarithm operation, the computational time for information retrieval is shortened by the proposed method. In addition, the hybrid three‐dimensional images of absorption and phase information were reconstructed using an absorption reconstruction algorithm, hence the existing data pre‐processing methods and iterative reconstruction algorithms in absorption reconstruction may be utilized in phase reconstruction immediately.